2000
DOI: 10.1007/s11627-000-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gelling agents on culture medium gel strength, water availability, tissue water potential, and maturation response in embryogenic cultures of Pinus strobus L.

Abstract: Maturation of somatic embryos of Pinus strobus L. was evaluated on media containing various types (agars and gellan gum), brands and concentrations of gelling agents in the presence of 80 mM ABA and 0.09 M sucrose. The media were characterized with respect to gel strength, water potential and water availability. Embryogenic tissue and somatic embryos cultured on medium with various concentrations of gellan gum were used to determine their water potential (C). Regardless of the type of gelling agent used, gel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 28 publications
7
58
0
2
Order By: Relevance
“…Saito and Nishimura (1994) and Magioli et al (2001) also observed highest conversion rates of SE on media solidified with phytagel, as compared to those solidified with agar. The use of phytagel could reduce water availability in the culture medium and contribute to desiccation (Klimaszewska et al, 2000;Choudhury et al, 2008), similarly to the natural process that occurs in most zygotic embryos (Bradford, 1994). Reduced water availability seems to modulate embryo metabolism inducing the synthesis of proteins and enzymes found in germinating seeds and is considered by some authors as the most important factor to improve germination of SE (Malabadi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Saito and Nishimura (1994) and Magioli et al (2001) also observed highest conversion rates of SE on media solidified with phytagel, as compared to those solidified with agar. The use of phytagel could reduce water availability in the culture medium and contribute to desiccation (Klimaszewska et al, 2000;Choudhury et al, 2008), similarly to the natural process that occurs in most zygotic embryos (Bradford, 1994). Reduced water availability seems to modulate embryo metabolism inducing the synthesis of proteins and enzymes found in germinating seeds and is considered by some authors as the most important factor to improve germination of SE (Malabadi et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The adverse effect of PEG has also been demonstrated in Picea abies (Bozkhov and von Arnold 1998). Somatic embryo maturation is also stimulated by high concentration of gellan gum (1%) in the presence of ABA (Klimaszewska et al 2000).…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 95%
“…Huang et al (2012) highlighted that endogenous auxin stimulate shoot regeneration in rice calli. Abscisic acid (ABA) supplemented medium produces high quality somatic embryos by decreased osmotic water potential compared to the maintenance medium (Klimaszewska et al, 2000;Pérez et al, 2015). Osmotic water potential depends on types of media, carbon sources and gelleting agent concentrations (Hadeler et al, 1995;Klimaszewska et al, 1997;Laine et al, 2000;Triqui et al, 2008).…”
Section: Introductionmentioning
confidence: 99%